Community of practice: an effective mechanism to strengthen capacity in climate change and health - El Amiri, Nisrine (Can J Public Health, 2020)
SETTING: Climate change is one of the greatest threats to global health in the twenty-first century and has recently been declared a health emergency. The lack of effective dissemination of emerging evidence on climate change health risks, effects, and innovative interventions to health professionals presents one of the greatest challenges to climate action today. INTERVENTION: To identify and address the knowledge gaps at the intersection of health and climate change, the Canadian Coalition for Global Health Research (CCGHR) established a Working Group on Climate Change and Health (WGCCH). WGCCH is evolving organically into a community of practice (CoP) that aims to elevate knowledge brokering on climate change and health and expand to global multi-, inter-, and transdisciplinary realms. OUTCOMES: To date, the WGCCH established a regular webinar series to share expert knowledge from around the world on intersections between climate change and health, developed short summaries on climate change impacts on broad health challenges, supported young professional training, and enhanced climate health research capacity and skills through collegial network development and other collaborative projects that emerged from CoP activities. IMPLICATIONS: This paper proposes that WGCCH may serve as an example of an effective strategy to address the lack of opportunities for collaborative engagement and mutual learning between health researchers and practitioners, other disciplines, and the general public. Our experiences and lessons learned provide opportunities to learn from the growing pains and successes of an emerging climate change and health-focused CoP.